1996
DOI: 10.1095/biolreprod54.6.1217
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Soluble Human Complement Receptor Type 1 Inhibits Antisperm Antibody- and Neutrophil-Mediated Injury to Human Sperm1

Abstract: The pathogenesis of antisperm antibody (ASA)-mediated infertility is postulated to be related in part to complement (C)-dependent sperm dysfunction in the female genital tract. We have previously demonstrated that C can be involved in ASA-mediated sperm injury by the deposition of activated C3 fragments and the assembly of terminal membrane attack complex (C5b-9) leading to C3-mediated sperm binding to neutrophils or C5b-9-mediated sperm motility loss. This study evaluated the protective effect of recombinant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 39 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…The female reproductive tract is abundant in complement, partly because it requires a periodic removal mechanism for millions of allogeneic spermatozoa. One reported detrimental effect of complement on sperm in the female reproductive tract is that females who produce antisperm antibody become infertile when the antibody inactivates sperm with complement (8). It is also reported that the estrogen stimulates the synthesis of C3 in rat uterus (38).…”
mentioning
confidence: 99%
“…The female reproductive tract is abundant in complement, partly because it requires a periodic removal mechanism for millions of allogeneic spermatozoa. One reported detrimental effect of complement on sperm in the female reproductive tract is that females who produce antisperm antibody become infertile when the antibody inactivates sperm with complement (8). It is also reported that the estrogen stimulates the synthesis of C3 in rat uterus (38).…”
mentioning
confidence: 99%